Потенциал интеграции когенерационных систем в малую энергетику Украины - Маляренко, Виталий Андреевич; Шубенко, Александр Леонидович; Сенецкий, Александр Владимирович; Темнохуд, И. А. (Национальный технический университет "Харьковский политехнический институт", 2012)
Досліджуються питання доцільності реалізації комбінованого виробництва теплової та електричної енергії – когенерації. Показано, що застосування когенерації дозволяє більш ефективно використовувати ПЕР. Проведений аналіз показав, що питома витрата палива на виробництво електроенергії, при реалізації міні-ТЕЦ на парових котелень в середньому складає 180 г.у.п./(кВт·г). Проаналізовано, яка кількість турбін потужністю 0,75–1,5 МВт можливо реалізувати в Україні до 2030 р., тим самим економити в рік ~ 1,2 млн. т.у.п.

The issues of the expediency realization of the combined production of heat and power supply – the cogeneration. It is shown, that the application of co-generation allows to use the heat and power resources more effectively. The carried out analysis showed, that the specific waste of fuel per production of power energy on condition of realization of heat and power main (HPM)on the basis of steam boiler-houses at the average compose 180 grams of specific fuel per k/V per hour. It has been analyzed, what number of turbines 0,75–1,5 MVt is possible to sell in Ukraine by the year of 2030, namely to economize per year ~ 1,2 million of tons of specific fuel.
The integration potential of the co-genrrational systems in the framework of the light power industry of Ukraine
Keywords: энергосбережение; малая энергетика; мини-ТЭЦ; когенерация